Senescent HUVECs-secreted exosomes trigger endothelial barrier dysfunction in young endothelial cells - Wong, Pooi Fong; Tong, Kind Leng; Jamal, Juliana; Khor, Eng Soon; Lai, Siew Li; Mustafa, Mohd Rais (Leibniz Research Centre for Working Environment and Human Factors, 2019)
Accumulation of senescent endothelial cells can cause endothelium dysfunction which eventually leads to agerelated vascular disorders. The senescent-associated secretory phenotype (SASP) cells secrete a plethora of soluble factors that negatively influence the surrounding tissue microenvironment. The present study sought to investigate the effects of exosomes, which are nano-sized extracellular vesicles known for intercellular communications secreted by SASP cells on young endothelial cells. Exosomes were isolated from the condition media of senescent human umbilical vein endothelial cells (HUVECs) and then confirmed by the detection of exosome specific CD63 and CD9 expressions, electron microscopy and acetylcholinesterase assay. The purified exosomes were used to treat young HUVECs. Exposure to exosomes repressed the expression of adherens junction proteins including vascular endothelial (VE)-cadherin and beta-catenin, decreased cell growth kinetics and impaired endothelial migration potential of young endothelial cells. These findings suggest that senescent HUVECs-secreted exosomes could disrupt barrier integrity that underpins endothelial barrier dysfunction in healthy young endothelial cells. © 2019, Leibniz Research Centre for Working Environment and Human Factors. All rights reserved.